SP0121 Tapering in psa – to do or not to do?. (12th June 2018) - Coates, L.
Abstract : This talk will discuss the current evidence regarding tapering or drug withdrawal in patients with psoriatic arthritis. With increasing numbers of patients achieving good outcomes such as remission, the issue of how long to continue treatment for has been raised. Given the cost of some of the newer therapies, this question also has significant cost effectiveness implications. There is a limited amount of evidence but data from randomised and observational studies will be discussed as well as key research questions that remain outstanding. Disclosure of Interest: None declared